(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Wetlands are the most important natural function of the terrestrial surface of the earth. It is a habitat of many aquatic plants and animals. On the other hand in industrialization is the processes of human development . In India the industrial activities have been rapidly increasing and urbanization process has also been fastest growing. Due to the industrial activities negative impacts on nature. In the study area the Duwani wetland is the most valuable and productive wetland of Assam. Because this natural wetland is connected with the mighty Brahmaputra river. The industrial activities on the bank of this wetland have mostly polluted the soil function. In this research works soil quality of the wetland is tasted on laboratory. Various parameters have taken for analysis. Some of the parameters like Potential of Hydrogen (pH), Electrical Conductivity (EC), Organic Carbon (OC), Nitrogen ( N), Potassium ( K), Phosphorus (P), Chloride (Cl ) etc. The soil samples are measuring both the WHO and USPH standard. From this analysis have found the amount of soil pollution and functional ecosystem of Duwani wetlands